2019
DOI: 10.1111/ffe.13149
|View full text |Cite
|
Sign up to set email alerts
|

Fatigue strength prediction of carburized 12Cr steel alloy: Effects of evaluation of maximum crack sizes and residual stress distribution

Abstract: Axial loading fatigue tests of carburized 12Cr steel alloy in long‐life regime were performed under stress ratios of −1 and 0. Fatigue fracture can be divided into surface failure, interior failure without fine granular area (FGA), and interior failure with FGA. By considering the effects of the tensile limit, the evaluation of maximum crack sizes (inclusion sizes and FGA sizes), and residual stress distribution, the fatigue strength prediction model of carburized 12Cr steel alloy for inclusion‐FGA‐fisheye ind… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 34 publications
0
0
0
Order By: Relevance
“…According to Northwood et al [22], the amount of retained austenite and the residual stress increase as the carbon content increases, and they decrease after tempering. Deng et al [23] found that as the carburizing temperature and carbon potential increase, the amount of carbon in the carburized layer increases, which in turn leads to an increase in residual stress and inhibits the initiation of cracks. Yang et al [24] studied the calculation model for retained austenite, martensite, and residual stress by using the finite element method under different carburizing processes.…”
Section: Introductionmentioning
confidence: 99%
“…According to Northwood et al [22], the amount of retained austenite and the residual stress increase as the carbon content increases, and they decrease after tempering. Deng et al [23] found that as the carburizing temperature and carbon potential increase, the amount of carbon in the carburized layer increases, which in turn leads to an increase in residual stress and inhibits the initiation of cracks. Yang et al [24] studied the calculation model for retained austenite, martensite, and residual stress by using the finite element method under different carburizing processes.…”
Section: Introductionmentioning
confidence: 99%